PELATIHAN PENGOLAHAN SAMPAH ORGANIK DENGAN KONSEP ECO-ENZYM - Puguh Sujarta; Maria Ludia Simonapendi (JURNAL PENGABDIAN PAPUA, 2021)
Nutritional needs for humans in addition to staple food, the need for vitamins as additional food such as fruit. Consumption of fruits will produce fruit skin waste. Garbage is a problem for human life in the world. Unlike the case with organic waste, organic waste for Dr. Poompanvong can be converted into an eco-enzyme. Eco-enzyme is a multifunctional liquid produced from the fermentation of waste or organic waste, brown sugar / granulated sugar, and water. Eco-enzyme is a magic liquid whose benefits are very environmentally friendly, such as in the production process of eco-enzymes to produce O3 gas (the same as planting 10 trees), one liter of eco-enzyme solution can purify contaminated rivers, as an antiseptic and fertilize the soil. The objectives of implementing this community service activity are: first to introduce an organic waste management program with the concept of eco-enzymes; second, through dedication can produce output in the form of a national journal. This activity was held on July 28, 2020 at SMA Teruna Bhakti Waena Jayapura City and July 30, 2020 at SMA Negeri 2 Skanto Keerom. The target audience involved in this activity is high school students. The selection of target audiences is based on the duties and obligations of students to build Adiwiyata High School that loves the environment. The methods used in the implementation of the activity are lectures, simulations and practices on organic waste processing with the concept of eco-enzymes. The conclusion was that the participants were enthusiastic and knew the results of organic waste products with the concept of eco-enzymes. Based on the results of the evaluation, it shows that the level of participant satisfaction is high when viewed from the percentage of all aspects. Keywords: organic waste; eco-enzym; adiwiyata; Jayapura; Keerom